Endothelin 1 and 3 enhance neuronal nitric oxide synthase activity through ETB receptors involving multiple signaling pathways in the rat anterior hypothalamus - Jaureguiberry, María Soledad (2004)
We have previously reported that endothelin 1 and 3 (ET-1, ET-3) through the ETB receptor decrease norepinephrine release in the anterior hypothalamus and activate the nitric oxide (NO) pathway. In the present work we sought to establish the receptors and intracellular mechanisms underlying the increase in nitric oxide synthase (NOS) activity stimulated by ET-1 and ET-3 in the rat anterior hypothalamus. Results showed that ETs-stimulated NOS activity was inhibited by a selective ETB antagonist (BQ-788), but not by a selective ETA antagonist (BQ-610). In addition, NOS activity was not altered in the presence of an ETA agonist (sarafotoxin 6b), but it was enhanced  in the presence of a ETB agonist (IRL-1620). Both N-nitro-l-arginine methyl ester (NOS inhibitor), and 7-nitroindazole (neuronal NOS inhibitor) diminished ETs-stimulated NOS activity. The stimulatory effect of ETs on NOS activity was inhibited in the presence of PLC, PKC, PKA and CaMK-II inhibitors (U-73122, GF-109203X, H-89 and KN-62, respectively), and the IP3 receptor selective antagonist, 2-APB. Our results showed that both ET-1 and ET-3 modulate neuronal NOS activity through the ETB receptor in the rat anterior hypothalamus involving the participation of the PLC-PKC/IP3 pathway as well as PKA and CaMK-II.B receptor decrease norepinephrine release in the anterior hypothalamus and activate the nitric oxide (NO) pathway. In the present work we sought to establish the receptors and intracellular mechanisms underlying the increase in nitric oxide synthase (NOS) activity stimulated by ET-1 and ET-3 in the rat anterior hypothalamus. Results showed that ETs-stimulated NOS activity was inhibited by a selective ETB antagonist (BQ-788), but not by a selective ETA antagonist (BQ-610). In addition, NOS activity was not altered in the presence of an ETA agonist (sarafotoxin 6b), but it was enhanced  in the presence of a ETB agonist (IRL-1620). Both N-nitro-l-arginine methyl ester (NOS inhibitor), and 7-nitroindazole (neuronal NOS inhibitor) diminished ETs-stimulated NOS activity. The stimulatory effect of ETs on NOS activity was inhibited in the presence of PLC, PKC, PKA and CaMK-II inhibitors (U-73122, GF-109203X, H-89 and KN-62, respectively), and the IP3 receptor selective antagonist, 2-APB. Our results showed that both ET-1 and ET-3 modulate neuronal NOS activity through the ETB receptor in the rat anterior hypothalamus involving the participation of the PLC-PKC/IP3 pathway as well as PKA and CaMK-II.